Analisis Perilaku Membaca Label Halal dan Pangan Mahasiswa Indonesia: Studi Kasus Mahasiswa FTB UBTH: The Analysis of Indonesian Students’ Behavior in Reading Halal and Food Labels: A Case Study of FTB UBTH Students - Ismaya, Pandu Legawa; Faturochman, Hadi Yusuf; Nur’aqiilah, Syahla (Jurnal Ilmiah Pangan Halal, 2025)
Changes in lifestyle and increased consumption of packaged foods have prompted consumers, particularly students, to understand halal labels and food labels as a reference for choosing products. This study aims to determine the level of knowledge and compliance of students at the Faculty of Technology and Business, Bakti Tunas Husada University, in reading these labels. The study was conducted using a survey method with a questionnaire that had been validated and tested for reliability. The sample was determined using the Slovin formula, involving 71 respondents from semesters 2, 4, and 6 through multistage sampling. Descriptive analysis using SPSS included mean, minimum, maximum, and standard deviation values. The results showed that the majority of respondents were female (59.15%), aged 19–21 years (47.89%), and had a monthly allowance of >Rp1,000,000 (43.66%). The level of knowledge related to halal and food labels was mostly in the good category (43.66%), while compliance with reading labels was dominated by the sufficient category (53.52%). These findings indicate that although students’ knowledge is relatively good, the habit of reading labels is still not optimal. Continuous education is needed to improve compliance with reading labels for food safety and health.